Socialization for the Formation of Young Generation Discipline - Ginanjar Wira Saputra; Shinta Dzauharoh; Ahmad Johan; Mohammad Fauzi Kusumawardana; Susilawati Susilawati (TGO Journal of Community Development, 2023)
This activity aims to socialize Character Building activities at Bandung University in improving student discipline. This activity method involves analyzing quantitative and qualitative data from the results of surveys and interviews involving students, heads of study programs, and academic personnel. Socialization results show a significant increase in student discipline, reflected in positive changes in behavior, participation in academic activities, and involvement in social projects. Student awareness of the values of discipline and responsibility also increases, creating a more positive academic atmosphere. The implication of this research is that the Character Building program is effective as a character formation strategy, which can be a basis for further development. This research also highlights the importance of involving students directly in outreach and emphasizes the need for ongoing monitoring to identify long-term changes. Practical implications include continued improvements in program socialization and attention to multiple dimensions of the student experience.